2020
DOI: 10.3390/app10072541
|View full text |Cite
|
Sign up to set email alerts
|

Research on Semi-Active Vibration Control of Pipeline Based on Magneto-Rheological Damper

Abstract: This paper proposes a scheme to control the low-frequency vibration of pipelines by using magneto-rheological (MR) vibration reduction technology. The state equation and the transfer function of the pipeline system are established, and its stability and the sinusoidal excitation response are analyzed. The prototype of MR damper is developed. The dynamic characteristics of MR damper are tested and the double-sigmoid model of MR damper is established. The two-state control, Proportion Integration Differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Boily et al [2] investigated the impact of viscoelastic and porous materials on vibration and noise reduction of cylindrical shells. Ji et al [3] proposed a method to control the vibration of pipelines by using magnetorheological (MR) vibration reduction technology. Zhang [4] proposed to control the vibration of the cylindrical shell by periodically or nonperiodically-attached dynamic vibration absorber (DVA).…”
Section: Introductionmentioning
confidence: 99%
“…Boily et al [2] investigated the impact of viscoelastic and porous materials on vibration and noise reduction of cylindrical shells. Ji et al [3] proposed a method to control the vibration of pipelines by using magnetorheological (MR) vibration reduction technology. Zhang [4] proposed to control the vibration of the cylindrical shell by periodically or nonperiodically-attached dynamic vibration absorber (DVA).…”
Section: Introductionmentioning
confidence: 99%
“…Praveen et al (2020) studied the torsional vibration isolation characteristics of MR elastomer and studied the vibration isolation effects of MR elastomer in semi-stationary systems using modal analysis methods. Ji et al (2020) proposed a scheme to control low-frequency vibration of pipelines using magneto-rheological vibration damping technology. The study results showed that the amplitude attenuation rate and acceleration attenuation rate can reach 92.34% and 84.77% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At present, it has become a new generation of civil engineering structural vibration damping devices and has been initially used in civil engineering structural vibration control. Ji et al [2] proposed a scheme of using MR damping technology to control pipeline vibration. e test results show that all three pipeline vibration control methods based on MR dampers can effectively control pipeline vibration.…”
Section: Introductionmentioning
confidence: 99%